Hubungan Antara Harga Diri dan Kelekatan Terhadap Orang Tua dengan Kecemasan Sosial pada Remaja Gen Z Pengguna Media Sosial - Annisa Ramadhani; Iranita Hervi Mahardayani (Universitas Muhammadiyah Metro, 2026)
The intensive use of social media among Generation Z adolescents has created new psychosocial challenges, particularly in relation to social comparison, self-presentation, and anxiety in social interaction. Social anxiety may be influenced by internal psychological factors such as self-esteem and relational factors such as parental attachment. This study aimed to examine the relationship between self-esteem and parental attachment with social anxiety among Generation Z adolescents who actively use social media. A quantitative correlational design was employed. The participants consisted of 48 adolescents aged 17–27 years who had passed the data cleaning process and used social media regularly. Data were collected through online Likert-scale questionnaires measuring social anxiety, self-esteem, and parental attachment. The instruments demonstrated strong internal consistency, with Cronbach’s alpha values of 0.956 for the Social Anxiety Scale, 0.920 for the Self-Esteem Scale, and 0.928 for the Parental Attachment Scale. Data were analyzed using multiple regression and product–moment correlation after the assumptions of normality and linearity were fulfilled. The results showed that self-esteem and parental attachment were simultaneously and significantly related to social anxiety (R = 0.433; RÂ² = 0.187; F = 5.191; p = 0.009), explaining 18.7% of the variance in social anxiety. Partial analysis also indicated significant relationships between self-esteem and social anxiety (r = 0.354; p = 0.007) and between parental attachment and social anxiety (r = 0.381; p = 0.004). These findings suggest that self-esteem and parental attachment are important psychosocial factors associated with social anxiety among Generation Z adolescents in the context of social media use. This study provides practical implications for school counselors, parents, and mental health practitioners in developing preventive programs that strengthen self-esteem, improve parent–adolescent relationships, and reduce social anxiety in the digital era.